DETERMINAN AKSES MEMPEROLEH KONDOM PADA KALANGAN LELAKI SEKS LELAKI DI INDONESIA - Mona S Fatiah (JURNAL KESEHATAN REPRODUKSI, 2023)
Abstract Background: Access to condoms is an important intervention in preventing HIV transmission among key populations, particularly Men who have Sex with Men (MSM), as they represent the highest group living with HIV in Indonesia. Objective: To investigate the determinants of access to condoms among MSM. Method: This study employed a cross-sectional design and used data from the 2018-2019 Integrated Biological and Behavioral Survey (IBBS) conducted in 24 provinces in Indonesia. The study population consisted of 4,290 individuals selected using Respondent Driven Sampling (RDS) technique. After data collection, multivariate predictive modeling analysis was conducted using STATA 14 software. Results: The study found that exposure to HIV information (OR: 1.64 with 95% CI: 1.18-2.28), perceived risk of HIV transmission (OR: 1.69 with 95% CI: 1.29-2.20), and consistent condom use (OR: 4.06 with 95% CI: 3.03-5.45) were significant determinants of access to condoms among MSM. The most dominant variable was consistent condom use during sex. Conclusion: MSM who have a good understanding of HIV, perceive their risk of HIV transmission, and consistently use condoms during sexual intercourse are more likely to have access to condoms. The study recommends interventions to increase MSM's knowledge about HIV and the need for monitoring and evaluation by various agencies to ensure the availability and ease of access to condoms for key populations. Keywords: Determinant; Access to condoms; Men who have Sex with Men (MSM)   Abstrak Latar belakang: Akses dalam memperoleh kondom merupakan salah satu bentuk intervensi dalam pencegahan penularan HIV pada kelompok populasi kunci, terutama Lelaki Seks Lelaki (LSL) mengingat LSL merupakan kelompok tertinggi yang hidup dengan HIV di Indonesia Tujuan: melihat determinan akses memperoleh kondom pada kalangan LSL Metode: Desain penelitian adalah desain cross sectional  dengan menggunakan data STBP 2018-2019 dimana penelitian ini dilakukan di 24 provinsi yang ada di Indonesia dengan sampel penelitian adalah total populasi berjumlah 4.290 orang. Teknik pengambilan sampel adalah Respondent Driven Sampling (RDS). Setelah data diperoleh, maka dilakukan analisis sampai dengan analisis multivariat model prediksi dengan menggunakan software STATA 14 Hasil: Hasil penelitian ini menemukan jika keterpaparan informasi tentang HIV (OR: 1,64 dengan nilai 95% CI: 1,18 – 2,28), risiko tertular HIV (OR: 1,69 dengan nilai 95% CI: 1,29 – 2,20) dan konsistensi penggunaan kondom (OR: 4,06 dengan 95% CI: 3,03 – 5,45). Variabel dominan adalah konsistensi penggunaan kondom. Kesimpulan: LSL yang memahami tentang konsep HIV dan memiliki persepsi risiko berisiko tertular HIV serta konsisten menggunakan kondom saat melakukan hubungan seks akan lebih mudah dalam mengakses kondom. penelitian ini merekomendasikan perlunya upaya intervensi dari segi peningkatan pengetahuan LSL tentang HIV serta perlunya monitoring dan evaluasi dari berbagai instansi untuk menjamin ketersediaan dan kemudahan akses kondom pada kelompok kunci. Kata kunci: Determinan; Akses memperoleh kondom; Lelaki Seks Lelaki (LSL)